Examining Islamic Religious Education Policy in Indonesia: A Multidimensional Theoretical Approach - Nasir, Abu; Tobroni (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
Islamic education in Indonesia must engage in various initiatives in order to enhance its comprehension of its position within the national education system. It is imperative for Islamic education to endorse and augment general education in grasping the complexities of the contemporary world, rather than concentrating solely on religious identity. National strategies need to acknowledge education as a critical element in addressing societal and environmental transformations. The analysis of Islamic education policies has commenced following the enactment of the National Education System Law in 2003. A more profound insight into these policies has the potential to fortify the education system, ensuring the adaptation of Islam in parallel with its doctrinal teachings. By catering to current requirements and fortifying the education sector, particularly Islamic education, there exists significant potential for substantial contributions to sustainable economic advancement and the fostering of human resources in Indonesia.